2019
DOI: 10.1530/ec-19-0246
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between BRAF V600E and clinical features in papillary thyroid carcinoma

Abstract: Objective To investigate the mutant status of BRAF gene and analyze its relationship to epidemiological risk factors and clinical outcomes among patients with papillary thyroid cancer (PTC) in the largest, single-institution Chinese cohort to date. Methods The medical records of 2048 PTC patients were reviewed in this retrospective study. Single-factor and multiple logistic regression analyses were applied to identify risk factors for BRAF V600E mutation. Survival outcomes including distant metastatic and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 31 publications
6
58
0
1
Order By: Relevance
“…Other studies detected BRAF V600E mutations in primary tumors in 48.5–83.7% of PTC cases, and BRAF V600E mutation frequency has increased in recent years ( 4 , 6 , 17 , 18 ). The BRAF V600E positivity in the current study is similar to the previous reports both in primary tumors ( 19 , 20 ) and in LNM ( 21 , 22 ). Some studies ( 9 , 21 ) found high concordance of the genotype between primary tumors and LNM in BRAF V600E mutations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other studies detected BRAF V600E mutations in primary tumors in 48.5–83.7% of PTC cases, and BRAF V600E mutation frequency has increased in recent years ( 4 , 6 , 17 , 18 ). The BRAF V600E positivity in the current study is similar to the previous reports both in primary tumors ( 19 , 20 ) and in LNM ( 21 , 22 ). Some studies ( 9 , 21 ) found high concordance of the genotype between primary tumors and LNM in BRAF V600E mutations.…”
Section: Discussionsupporting
confidence: 92%
“…First, a relatively small number of PTC patients from a single center were retrospectively analyzed, thus, there may be a selection bias in enrolled patients in our study. However, the BRAF V600E mutation frequency in the primary tumors in this study (81.5%) was similar to previous reports (83.7%) ( 19 , 20 ). Likewise, the BRAF V600E positivity in LNM was 78% in our study, which was similar to other studies (73.9, 81.0%) ( 21 , 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mRNA-based mutation detection assay, thus contributed to a 28% improvement in the sensitivity of detection, whereas the specificity of both the mRNA-and DNA-based assays was 100%. According to a number of studies, the prognostic relevance of BRAF V600E mutation still remains controversial in papillary thyroid carcinoma [23][24][25][26]. While the BRAF V600E mutation is not an independent predictor of poor outcome, the presence of the mutation is valuable for determining whether certain high-risk patients, in a relapse or primary metastatic setting, could be eligible for targeted BRAF inhibitor therapy with any of the currently available drugs, such as lenvatinib, vemurafenib or sorafenib [27].…”
Section: Discussionmentioning
confidence: 99%
“…Classical subtype, characterized by a papillary and follicular variant, has an excellent prognosis, while patients with aggressive histopatholologic features in the primary tumor are considered at risk of developing RAI-refractory DTC [ 5 ]. BRAF V600E is the most common mutation observed in DTC and triggers tumorigenesis through the mitogen-activated protein kinase (MAPK) pathway [ 6 ]. Multiple studies have shown BRAF V600E mutation is associated with poor clinicopathologic outcomes, larger tumor size, local recurrence and distant metastases [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%